Education For Prevention of Acute Hepatitis in School Children Al Bayan High School in Makassar - Suradi Efendi; Nour Sriyanah; Muh. Zukri Malik; Mikawati (PT Inovasi Pratama Internasional, 2022)
The issue of hepatitis Becomes problem important for society, parents and children for guard cleanliness environment and health they are wrong only one on junior high school students. By because that is, knowledge about acute hepatitis need integrated into the learning through chapter system digestion in class VIII SMP. one method for dig knowledge and attitude student to hepatitis issue. Activities devotion Public this located at SMP Al Bayan Makassar city Makassar . Activity this form education health about prevention of acute hepatitis on child done in form counseling use leaflets , lectures and ask answer on students grades 2 and 3 junior high school, total students / i as many as 58 people. Activity devotion Public this is carried out on day Friday, June 23, 2022. Results obtained students / i not yet understand about prevention of acute hepatitis , however after given education students capable knowing symptoms of acute hepatitis on child and understand prevention as well as proper handling.